FORMING STUDENTS' PREPAREDNESS TO USE ART IN SOCIAL WORK WITH ELDERLY PEOPLE - Fedotenko Inna Leonidovna (Arts Academy)
f students' preparedness to use various types of art in social work with the elderly. The author considers the essence, the structure of preparedness as a psychological and pedagogical phenomenon, the principles of organization of experimental work, reflecting the content of training. The author highlights the organizational and pedagogical conditions that stimulate the desire of students to use various types of art. The results of the study show that students were interested to include art into their palette of technologies they appropriated for social practice with elderly people. The purposeful formation of students' preparedness to use various types of art in social work contributed to several things: formation of their understanding of the aesthetic and humanistic nature of art, its potential in solving professional issues in a situation of uncertainty; improving the professionalism of future social workers; development of their moral and aesthetic qualities of personality.